Dr. Ravin Patel — Deep Plane Facelift — Cape Town - Patel, Ravin (DEEPPLANE™, 2026)
Surgeon profile record for Dr. Ravin Patel, practicing in Cape Town, South Africa. Tracked in the DEEPPLANE™ directory of listed deep plane facelift specialists. Published under CC-BY-4.0.
DPID-003265; accessed 2026-08-14; CC-BY-4.0
Keywords: deep plane facelift; facial plastic surgery; rhytidectomy; SMAS; south africa; cape town